KEBANGKITAN INDUSTRI HOSPITALITY DI KOTA BATAM PASCA PANDEMI COVID 2019 - Dailami; Moh. Thandzir (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2023)
Batam City, which at the beginning of its development was the establishment of the Batam Authority Board with the issuance of Presidential Decree No. 41 of 1973 concerning the Batam Island Industrial Area, which is currently the Batam City Concession Agency, has a strategic location, supported by good infrastructure facilities so that Batam City is the prima donna for domestic and foreign tourists. According to data from the Batam City Government, the number of tourist visits in 2019 before the Covid 19 Pandemic hit reached 6 million domestic tourists and 1.9 million foreign tourists. The Covid 19 pandemic that hit all countries in the world has eroded the Batam City tourism sector due to the imposition of health quarantine by every country with restrictions on people's movements and gatherings. At this time, after the 2019 covid pandemic, all parties, both the community in general, the government and tourism business people, hope and work hard to restore the Batam City tourism industry so that it can recover as before. Of course the support and development of the hospitality industry is an important factor for the advancement of Batam City tourism. The hospitality industry is a type of business or business that prioritizes customer satisfaction by being friendly, sincere and loving. The hospitality industry needs to pay attention to comfort by providing the best service, cleanliness, and so on other support such as the best food and drinks.